FROM TRADITIONAL TO DIGITAL ECONOMY: RESHAPING ANTI-CORRUPTION POLICIES FOR SUSTAINABLE DEVELOPMENT - KALASHNYK, Nadiia; KYRYLENKO, Pavlo (SSD Journal, 2025)
The article explores the transformative impact of digital tools and methodologies on anti-corruption efforts. Modern studies on social and administrative determinants of economic behavior were analyzed, and it was established that these studies have enhanced the efficacy of these measures through advanced data analysis and policy evaluation techniques, such as Randomized Controlled Trials (RCTs) and Instrumental Variables (IV). However, the article cautions against overreliance on quantitative methods and technology, emphasizing the need for ethical considerations and human judgment to address nuanced corruption. Transparent financial systems and blockchain technology are highlighted as pivotal in reducing corruption by enhancing traceability and accountability. Despite these advancements, challenges such as cybersecurity risks, implementation costs, and resistance from vested interests persist. The article advocates for a balanced approach that integrates technological innovations with ethical principles and systemic reforms to foster a transparent, accountable, and corruption-free digital society. It is argued that the new logic of anti-corruption policies is based on evidence-based policy research, the use of instrumental variables, the determination of causal relationships through natural experiments in anti-corruption policy and the economic behavior of all stakeholders, which is critically important for the effectiveness of anti-corruption measures. This article explores the dual role of digitalization in shaping modern anti-corruption strategies. On the one hand, transparency in financial transactions significantly deters corrupt behavior by increasing traceability and accountability. Blockchain technology, in particular, enhances trust by offering immutable records and decentralized control, limiting opportunities for manipulation. On the other hand, the adoption of digital solutions must be accompanied by careful consideration of their limitations, including cybersecurity vulnerabilities, implementation costs, and resistance from stakeholders benefiting from existing corrupt practices.